VIOLENCIA ESCOLAR EN LOS NIÑOS Y NIÑAS DE LA ESCUELA “GUSTAVO DARQUEA TERÁN” DE LA CIUDAD DE LOJA - Sinchire Chamba, Guissella Vanessa (2019)
School violence is a latent social problem in the educational context, where groups of students live day by day this situation, you can clearly identify the fear, which causes them, affecting their development and self-esteem. Given the importance of this phenomenon in our society arises the requirement to perform the present investigation entitled: “SCHOOL VIOLENCE IN THE CHILDREN OF THE SCHOOL “GUSTAVO DARQUEA TERÁN” OF THE CITY OF LOJA”, Raising as a general objective; Design a proposal focused on reducing school violence in children. The present investigation involved 42 children, 42 parents and 4 teachers from the "Gustavo Darquea Terán" school, the methodology used was based on the scientific, deductive, inductive, analytical and synthetic methods, through the use of of research techniques such as observation, structured interview, focus group and survey that allowed to fulfill the objectives set out in the research process. The main findings obtained in the research, establish that the causes of school violence are generally given by the family environment by poor communication, poor training in values such as respect, responsibility, companionship and tolerance towards others, as well as aggression intrafamiliares generate a perspective where children take violence as normal. Likewise, the consequences generated by school violence in children are low self-esteem as they feel excluded and fearful which in turn leads to having little relationship with others, fear o attend the school, feel fearful when doing educational activities, have poor skills to communicate with people in their social environment, school failure. Boys and girls mention that the places where school violence occurs is mainly in the classroom when there is no 5 presence of the teacher, also in the playground, in the playground, corridors and at the exit of the institution are other places where the types of violence are evidenced daily. Therefore, it is recommended that teachers and staff of the institution conduct awareness campaigns to students to prevent school violence